Policy Transformation for MSMEs Export Development Based on Local Potential: A Case Study of Yogyakarta City, Indonesia - Susanto Susanto; Ahmad Ma’ruf; Agus Tri Basuki (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
The transformation of MSMEs export policies based on local potential is a strategic effort to enhance regional economic competitiveness. This study analyzes the readiness and strategic direction of MSMEs export development in Yogyakarta City using SWOT analysis and the Eisenhower Matrix. A qualitative approach was applied, with data collected through in-depth interviews with MSMEs actors, policy document analysis, and secondary export data. SWOT analysis was employed to identify internal and external factors influencing MSMEs export performance, while the Eisenhower Matrix was used to prioritize strategies based on urgency and importance.The results indicate that MSMEs in Yogyakarta City have strong potential derived from creative and culture-based products, alignment with global market trends, and high entrepreneurial motivation. Nevertheless, export development is constrained by limited production capacity, weak access to financing, low compliance with international standards, and underdeveloped marketing and logistics systems. Priority strategies categorized as urgent and important include strengthening export capacity and production standards, accelerating international certification, improving financing and logistics efficiency, and enhancing digital marketing and global buyer networks. The study concludes that an integrated and adaptive policy framework is essential to strengthen MSMEs export competitiveness and ensure sustainable, locally driven export growth.